2022
DOI: 10.1002/cpt.2722
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Approach to Selecting Pegfilgrastim Dose for Pharmacokinetic and Pharmacodynamic Similarity Studies in Biosimilar Development

Abstract: This study applied modeling and simulation (M&S) approaches to evaluate the sensitivity of pegfilgrastim pharmacokinetics (PKs) and pharmacodynamics (PDs) to changes in dose amount, and linear or nonlinear clearance (CL) over pegfilgrastim subcutaneous dose of 2-6 mg. A previously published model was adapted to better describe pegfilgrastim PK and PD data in healthy subjects and used in simulation. Nonlinear CL accounts for 98% and 77%, respectively, of the total CL of pegfilgrastim at 2 and 6 mg. The sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Model-based Testing Markers [204] The FDA has also presented results on a Model-Based Approach for the Dose Selection of P e g f i l g r a s t i m , w h i c h t r e a t s n e u t r o p e n i a ( l o w w h i t e b l o o d c e l l c o u n t ) c a u s e d b y a n t i c a n c e r medications. There are several approved biosimilars for which PK and PD approaches, using the absolute neutrophil count biomarker, have been used to support biosimilar approval.…”
Section: Fda Researchmentioning
confidence: 99%
“…Model-based Testing Markers [204] The FDA has also presented results on a Model-Based Approach for the Dose Selection of P e g f i l g r a s t i m , w h i c h t r e a t s n e u t r o p e n i a ( l o w w h i t e b l o o d c e l l c o u n t ) c a u s e d b y a n t i c a n c e r medications. There are several approved biosimilars for which PK and PD approaches, using the absolute neutrophil count biomarker, have been used to support biosimilar approval.…”
Section: Fda Researchmentioning
confidence: 99%
“…The primary results of these three trials are reported by Sheikhy et al (PSCK9 inhibitors), 5 Gershuny et al (IL-5 antagonists), 4 and Florian et al (interferon beta-1a products), 3 and Hyland et al reports the results of an evaluation of the utility of proteomics for identifying PD biomarkers from the interferon clinical trial. 14 In addition, Li et al 6 describe a model-based approach to inform dose selection, and Vaidyanathan et al 15 describe the evolution of regulatory requirements for insulin products to the current standard that stipulates PK and PD similarity data are sufficient to support approval of biosimilar insulin products.…”
Section: Using Pd Biomarkers and Midd As An Alternative To Comparativ...mentioning
confidence: 99%
“…One way to do this is to leverage the use of pharmacodynamic (PD) biomarkers in clinical pharmacology studies in place of comparative clinical studies with efficacy end point(s), which is discussed in multiple articles in this issue 1–5 . These articles and others 6 also discuss how modeling and simulation (or model‐informed drug development (MIDD)) can be used to optimize study design and analyses. Other articles focus on characterizing the relationship between product quality characteristics (e.g., structural and functional characterization) and clinical performance to further streamline clinical development 7–9 .…”
Section: Reference Product United States European Union Canada Japanmentioning
confidence: 99%
See 1 more Smart Citation